Hypoxia Inducible Factor-1α (HIF-1α) Mediates NLRP3 Inflammasome-Dependent-Pyroptotic and Apoptotic Cell Death Following Ischemic Stroke. (10th November 2020) - Jiang, Qian; Geng, Xiaokun; Warren, Jonathan; Eugene Paul Cosky, Eric; Kaura, Shawn; Stone, Christopher; Li, Fengwu; Ding, Yuchuan
Graphical abstract: Highlights: Activation of NLRP3 inflammasome subsequently activates pyroptosis and apoptosis. HIF-1α mediates NLRP3 inflammasome-dependent-pyroptotic and apoptotic cell death. Inhibition of HIF-1α alleviates NLRP3/caspase-1 and rescues immune cell infiltration. Abstract: Stroke is a major cause of death and long-term disability. Recent evidence suggests that hypoxia-inducible factor 1α (HIF-1α), a transcription factor that regulates oxygen levels, plays a key role in neurological outcomes after ischemic stroke. Accordingly, we investigated the mechanism of HIF-1α on pyroptotic and apoptotic cells during ischemia/reperfusion (I/R). Adult Sprague-Dawley rats underwent 2 h of middle cerebral artery occlusion (MCAO). The rats were then exposed to 6 or 24 h of reperfusion, with or without YC-1 (HIF-1α inhibitor, 5 mg/kg). Infarct volumes, along with mRNA and protein quantities of HIF-1α, NLRP3, IL-1β, IL-18, Caspase-1, and co-localization of HIF-1α, and NLRP3, were assessed. We measured apoptotic and pyroptotic cell death, gasdermin D (GSDMD) activation and lactate dehydrogenase (LDH) activity, and the infiltration of neutrophils and macrophages after ischemic stroke. HIF-1α mRNA and NLRP3 inflammasome components were increased after 24 h of reperfusion. YC-1 significantly reduced the mRNA and protein expression of NLRP3, IL-1β, IL-18, and caspase-1; significantly decreased infarction and pyroptotic cell death after 24 h of reperfusion; attenuated the neuroinflammatory response by reducing infiltration of CD68- and MPO-positive cells after 24 h of reperfusion; and reduced apoptotic cell death following ischemic stroke. We found that HIF-1α likely regulates inflammatory responses through the NLRP3 inflammasome complex, thus influencing both apoptotic and pyroptotic cell death after stroke. These findings suggest that future investigations are needed regarding HIF-1α and its role as a potential molecular target in the treatment of acute ischemic stroke.